Employees' perception on human resource information system in human resource department of higher learning institution - Denise, Wong. (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study was conducted to explore the employees' perception toward human resource information system in the organization. The effect of human resource information system would be measure on multiple variables in human resource manager job prospect such as human resource functions, time spent on human resource, human resource costs, decisionmaking and human resource information. The research methodology used is a quantitative questionnaire approach, distributing questionnaire to respondents. Statistical analyses used include Pearson Correlation will be used.